1986
DOI: 10.1136/adc.61.7.677
|View full text |Cite
|
Sign up to set email alerts
|

Renal handling of phosphate in the first six months of life.

Abstract: SUMMARY Indices of renal excretion and reabsorption of phosphate were studied in 20 neonatal infants, 20 infants aged 3 months, and 20 infants aged 6 months. All subjects were normal and were fed a modified formula enriched with vitamin D. In neonatal infants all indices of phosphate excretion were found to be significantly lower and those of phosphate reabsorption significantly higher than in older infants. Phosphate excretion gradually increased with age, while its reabsorption decreased. The positive correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…The 97th centile simplify calculation of TmPO4IGFR.5 ralue in our study of 069 mmol:mmol is close There are some differences seen between our o the value of 0-74 mmol:mmol obtained by study and other published data on TmPO4/GFR ihazali and Barratt6 so it would appear that in children." 12 Kruse et al demonstrated an ralues of this magnitude can be applied to inverse correlation between TmPOJ4GFR and British children but may not be applicable to age which was not seen in our study. " This may ther population groups.…”
Section: Discussionmentioning
confidence: 53%
“…The 97th centile simplify calculation of TmPO4IGFR.5 ralue in our study of 069 mmol:mmol is close There are some differences seen between our o the value of 0-74 mmol:mmol obtained by study and other published data on TmPO4/GFR ihazali and Barratt6 so it would appear that in children." 12 Kruse et al demonstrated an ralues of this magnitude can be applied to inverse correlation between TmPOJ4GFR and British children but may not be applicable to age which was not seen in our study. " This may ther population groups.…”
Section: Discussionmentioning
confidence: 53%
“…We have found a positive cor relation of TP/GFR with serum phosphorus as it was demonstrated for TmPOVGFR [9], In adults, TmPOVGFR varies little with di etary phosphorus [19], However, in spite of the very low phosphaturia after feeding pooled human milk, our study demonstrates that TP/GFR remains too low for age [12]. It is in contradiction with the results of Bistarakis et al [9] who found that phosphate indices were in no way different in breast-fed babies or babies fed unmodified cow milk [9], In spite of immaturity of the kidney of the pre term infant, its adaptation with modifying phosphorus load is remarkable. After 3 days of feeding milk formula adapted for preterm babies, which contains more proteins, cal cium and phosphorus with adequate Ca/P ratio, TP/GFR reached normal values for age and then remained stable.…”
Section: Discussionmentioning
confidence: 73%
“…In clinical practice, this pa rameter is calculated in adults using an em piric normogram described by Bijvoet et al [10] and by Walton and Bijvoet [11]. This normogram was, however, used in pediatric subjects to define normal values for renal phosphate handling [8,9]. In infancy, the serum concentrations of inorganic phospho rus are much higher, and the applicability of this normogram is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this, the renal threshold for phosphate concentration was 1.18 mmol/100 mL glomerular filtration rate (GFR), which was higher than the normal range for infancy (reference range 0.15-0.34 mmol/100 mL GFR), suggesting that he was not losing phosphate in the urine. 13 , 14 …”
Section: Case Presentationmentioning
confidence: 99%